2015
DOI: 10.1097/jsm.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Virtual Reality Balance Module for Use in Clinical Concussion Assessment and Management

Abstract: Objective To determine the criterion and content validity of a virtual reality (VR) balance module for use in clinical practice. Design Retrospective, VR balance module completed by participants during concussion baseline or assessment testing session. Setting A Pennsylvania State University research laboratory Participants A total of 60 control and 28 concussed students and athletes from the Pennsylvania State University Interventions None Main Outcome Measures This study examined: (1) the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…The VR balance module used in this study has previously been shown as a valid postural stability assessment tool. 22 In two studies using D-1 college football players, it was shown that there are no differences between VR final balance scores over three separate testing sessions as well as scores before and following a full practice. 18 More formal reliability statistics, such as intraclass correlation coefficients, have yet to be established for this technology.…”
Section: Discussionmentioning
confidence: 99%
“…The VR balance module used in this study has previously been shown as a valid postural stability assessment tool. 22 In two studies using D-1 college football players, it was shown that there are no differences between VR final balance scores over three separate testing sessions as well as scores before and following a full practice. 18 More formal reliability statistics, such as intraclass correlation coefficients, have yet to be established for this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Many diagnostic tests have been shown to reliably detect deficits in postural control in a concussed population [14,25,29]. Common tests include the Balance Error Scoring System (BESS) and the Sensory Organization Test (SOT) [6], while others include advanced technology such as the use of virtual reality [32,33,35,36]. Objective outcome measures with high sensitivity and specificity often require costly instruments such as high-resolution cameras and force plates that are not readily available on the sideline.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumented balance platforms that measure center of pressure (COP) excursions during static stance are commonly utilized to identify adaptations in balance and postural control that occur following injury and rehabilitation. [1][2][3] For clinical purposes, it is essential that balance platforms demonstrate reliability and validity to detect changes in postural control due to losses of visual input, vestibular input, and/or somatosensory input.…”
mentioning
confidence: 99%
“…[3][4][5] Force-plates calculate COP excursions using load cells and measuring the 3-dimensional (x, y, z) forces and moments generated between the foot and platform during stance.…”
mentioning
confidence: 99%